PENGARUH SUPLEMENTASI PROBIOTIK ISI RUMEN KERBAU DENGAN LEVEL BERBEDA TERHADAP NILAI KECERNAAN DAN TDN PADA DOMBA BALIBUL - Sutrisno; Surono; Kamilia Afliha (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2020)
This research was aimed to examine dry matter digestibility (DMD), organic matter digestibility (OMD) and total digestible nutrients (TDN) in balibul lambs which received complete feed supplemented with different levels of buffalo rumen contents as probiotic. Material used in this study were 16 heads of thin-tailed lamb males aged under 5 months with initial average body weight of 11.52 ± 0.78 kg. Experimental design used was completely randomized design (CRD) with 4 treatments dan 4 replications. Treatments applied were T0 (complete feed without buffalo rumen content), T1 (complete feed with 5% buffalo rumen contents), T2 (complete feed with 10% buffalo rumen contents) and T3 (complete feed with 15% buffalo rumen contents). Parameters observed were DMD, OMD and TDN. Result of the research showed that feeding of complete feed containing different level of buffalo rumen content as probiotic did not significantly affect DMD and OMD in lambs (P > 0.05), but significantly affected TDN values in lambs ​​(P < 0.05). It was concluded that different level of buffalo rumen contents as probiotics did not significantly affect on DMD and OMD values. TDN value of feed increased with the use of 5% buffalo rumen contents as probiotics compared to more than 5% level of buffalo rumen contents as probiotics.